Hepcidin as a Marker of Anemia in Chronic Hepatitis C Infections (Medical Forum Monthly, 2024)
Objective: To determine the level of serum hepcidin and iron studies in patients of chronic hepatitis C with anemia and to calculate sensitivity, specificity, negative predictive value ,positive predictive value, diagnostic accuracy of serum hepcidin and to differentiate between patients of iron deficiency anemia and anemia of chronic disease.Study Design: Diagnostic Study.Place and Duration of Study: This study was conducted at the Department of Pathology, Post Graduate Medical Institute (PGMI) Lahore. Subjects were taken from Medical Outdoor / Liver Clinic, Lahore General Hospital from 01.06.2015 to 30.06.2016.Materials and Methods: The study included 70 diagnosed patients of chronic hepatitis C which were divided into IDA group and ACD group. The IDA group comprised of 17(73.91%) males and 6(26.09%) females, while in ACD group there were 39(82.98%) males and 8(17.02%) females. The parameters studied were blood hemoglobin, total iron binding capacity, serum iron, percent transferrin saturation, serum ferritin and serum hepcidin and subsequent data was recorded. Mean ± standard deviation, frequency distribution and percentages were calculated. Using serum ferritin as a standard 2x2 table was made to determine diagnostic accuracy of serum hepcidin.Results: In the present study mean hemoglobin, MCV, serum iron, TIBC, ferritin and hepcidin in IDA and ACD groups were 7.21 ± 1.29 g/dL ,8.69±0.86 g/dL, p-value < 0.001, 63.30 ± 8.04 fL and 86.51±6.61, p-value < 0.001, 30.98 ± 13.50, 34.36 ± 17.53 µg/dl, p-value > 0.05, 431.91±145.05 µg/dl and 230.51 ± 89.74 µg/dl, p-value < 0.001, 20.37± 4.08 and 154.07 ± 144.01, p-value < 0.001, 2.39 ± 1.39 and 15.17 ± 7.21 ng/ml, p-value < 0.001 respectively. The Sensitivity, Specificity, Positive Predictive Value and Negative Predictive Value of serum hepcdin levels was 91.3%, 87.23%, 77.78% and 95.35% respectively. Diagnostic accuracy of serum hepcdin levels was 88.57% with positive regression coefficient (beta) and hepcidin Odds ratio for Hepcidin was 71.750.Conclusion: Low levels of serum hepcidin levels are significantly associated with decreased iron parameters in iron deficient patients of chronic hepatitis C and hepcidin could be a useful indicator of iron deficiency anemia and to differentiate iron deficiency anemia from anemia of chronic disease. Patients with decreased hepcidin level might get benefit by the use of iron therapy.